Pengaruh Metode Latihan Game Terhadap Peningkatan Passing Bawah Dalam Bola Voli Atlet Pst Bengkulu - Aribowo, Fransiskus Hendra; Suwarni, Suwarni; Perdima, Feby Elra (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This study aims to determine the effect of game training methods on improving underhand passing in volleyball athletes of PST Bengkulu. This study uses a quantitative approach with an experimental design to measure the effect of game training on improving underhand passing skills of PST Bengkulu athletes. The subjects of the study consisted of 32 athletes who were divided into two groups. the experimental group that followed the drill training program and the control group that did not receive any special intervention. analysis of the initial test data (pre-test) of the game training method training group with a sample size of 32 obtained the highest score of 53, the lowest score of 41, an average of 46.96, a median of 47. the final test (post-test) of the underhand passing drill training group obtained the highest score of 59, the lowest score of 45, an average of 51.81, a median of 51.50, a standard deviation of 3.93. The results of the paired t-test showed a greater t-count value (10.14) compared to the t-table value (2.145), which indicated that the research hypothesis was acceptable. It can be concluded that the game training method has a significant influence on improving the underhand passing skills in volleyball of PST Bengkulu athletes.